Propagation and update of auditory perceptual priors through alpha and theta rhythms. (8th March 2021) - Ho, Hao Tam; Burr, David C.; Alais, David; Morrone, Maria Concetta
Abstract: To maintain a continuous and coherent percept over time, the brain makes use of past sensory information to anticipate forthcoming stimuli. We recently showed that auditory experience of the immediate past is propagated through ear‐specific reverberations, manifested as rhythmic fluctuations of decision bias at alpha frequencies. Here, we apply the same time‐resolved behavioural method to investigate how perceptual performance changes over time under conditions of stimulus expectation and to examine the effect of unexpected events on behaviour. As in our previous study, participants were required to discriminate the ear‐of‐origin of a brief monaural pure tone embedded in uncorrelated dichotic white noise. We manipulated stimulus expectation by increasing the target probability in one ear to 80%. Consistent with our earlier findings, performance did not remain constant across trials, but varied rhythmically with delay from noise onset. Specifically, decision bias showed a similar oscillation at 9 Hz, which depended on ear congruency between successive targets. This suggests rhythmic communication of auditory perceptual history occurs early and is not readily influenced by top‐down expectations. In addition, we report a novel observation specific to infrequent, unexpected stimuli that gave rise to oscillations in accuracy at 7.6 Hz one trial after the target occurred in the non‐anticipated ear. This new behavioural oscillation may reflect a mechanism for updating the sensory representation once a prediction error has been detected. Abstract : We asked participants to discriminate the ear‐of‐origin of a brief pure tone embedded in dichotic white noise and manipulated stimulus expectation by presenting the target with unequal probability to the two ears (80% vs. 20%). Our results show that even under high stimulus expectation, auditory perceptual priors are propagated via ear‐specific reverberations, manifested as rhythmic fluctuations of decision bias at alpha frequencies ( 9 Hz).